Effect of Nitrogen Gas Cold Plasma on Cotton Fabric Dyed with Reactive Dyes - Akbarpour, H.; Rashidi, A.; Yazdanshenas, M.E.; Tayebi, H. (Asian Journal of Chemistry, 2012)
In this paper, a bleached well cotton sample was dyed with cold and hot reactive dyes and subsequently, the dyed samples were exposed to plasma condition containing nitrogen gas at 1 and 5 min of plasma exposure time. The effect of plasma on surface morphology was studied by scanning electronic microscope. The K/S and L* a* b* values were evaluated using a reflective spectrophotometer and consequently, the experiments showed that the sample dyed with reactive yellow 3 and reactive yellow 105 enjoys dye fastness which decreases after being washed due to the increase in the operation time of plasma. In addition, the increase in plasma operation time at constant pressure would increase the destructing effect on the surface morphology of samples dyed with hot and cold reactive. Finally, the Fourier transform Infra-red spectroscopy test showed the effect of plasma operation on determining the dye fastness and the change in existent functional groups in fabric after being washed.